The Board of Directors' Role in Ensuring Effective Corporate Governance in Pakistani Firms - Zahoor, Sajjad; Tian, Ye (Annals of Human and Social Sciences, 2023)
This research aims to explore the connection between board qualities and sustained corporate success, addressing the existing ambiguity in corporate governance studies. While prior research has offered valuable insights, this study delves deeper into the factors influencing a board's success, intending to bridge the existing knowledge gap. Corporate governance literature has extensively examined the link between board qualities and organizational stability. However, the outcomes have been inconclusive. Despite the insightful contributions of previous studies, there remains a lack of comprehensive understanding regarding the elements that significantly impact a board's effectiveness. This study seeks to enhance our knowledge in this area by investigating a broad range of indicators that contribute to the success of boards. To achieve our objective, this study employed quantitative data derived from two written surveys. Participants included managers of unlisted firms and corporate governance experts. Through a meticulous analysis of these surveys, we aimed to gain a better understanding of the factors influencing board effectiveness. By utilizing both managerial and expert perspectives, our research approach provided a comprehensive view of the subject matter. These findings shed light on the complexity of factors influencing board performance. Notably, our study identified a diverse array of interrelated mechanical elements, such as competence and diversity, as well as behavioral factors, including norms, trust, attitude, and conduct. To enhance board performance and, consequently, organizational success, we recommend a holistic approach. This involves fostering competence and diversity within the board, while also nurturing positive norms, trust, attitude, and conduct among board members.